Bibliometric Analysis of the Role of Human Resource Motivation on Service Quality in the Optical and Eye Health Sector in the Yogyakarta Region from 2020 to 2025 - Sri Wahyu Budoyo Kusumo; Arraywed Wibowo; Ardhitya Furqon Wicaksono (Yayasan Az Zukhruf Cendikia, 2025)
Purpose – This study aims to analyze the development of scientific literature on the role of human resource (HR) motivation on service quality in the optical and eye health sector in the Yogyakarta region from 2020 to 2025. A bibliometric approach was used to identify publication trends, dominant keywords, institutional affiliations, and inter-topic relationships in relevant studies. Data were collected from three major databases: Scopus, Google Scholar, and Garuda, applying inclusion criteria to articles addressing the concepts of work motivation, service quality, and the context of optical clinics in Indonesia. Design/methodology/approach – The analysis revealed 78 articles meeting the criteria, with a peak publication rate occurring in 2023. The institutions with the highest number of contributors were Gadjah Mada University, Ahmad Dahlan University, and Yogyakarta Polytechnic of Health. The most frequently appearing keywords included: motivation, employee performance, service quality, and eye clinic Findings – The main findings indicate that intrinsic motivation, such as non-financial work rewards, a supportive work environment, and opportunities for self-development, significantly impacts customer service quality in optical clinics and stores. Research limitations/implications – This study provides an important scientific contribution to supporting strategic decision-making in human resource management in the optical sector, particularly in the local context of Yogyakarta. The practical implications of these findings encourage the implementation of human resource management strategies that emphasize sustainable work motivation to increase customer satisfaction and loyalty.